Mosquito-borne alphaviruses in Zambia: Isolation and characterization of Eilat and Sindbis viruses - Chadwic De’Sean Mears; Koshiro Tabata; Takuma Ariizumi; Bernard M. Hang'ombe; Yongjin Qiu; Hayato Harima; Masahiro Kajihara; William W. Hall; Michihito Sasaki; Hirofumi Sawa; Yasuko Orba (Virus Research, 2025)
Alphaviruses in the family Togaviridae include zoonotic arthropod-borne viruses, including Sindbis virus (SINV), chikungunya virus, as well as insect-specific viruses such as Eilat virus (EILV). Previous investigations of alphaviruses in Zambia have identified a novel insect-specific alphavirus, Mwinilunga alphavirus in mosquitoes. Further ongoing surveillance resulted in the isolation of EILV and SINV for the first time in Zambia. Here, these alphaviruses were characterized in terms of growth kinetics in cells, and molecular phylogenetic relatedness to other alphaviruses. Zambian EILV (strain zmq19_M44) exhibited a close phylogenetic relationship with other insect-specific alphaviruses and shared a close nucleotide identity to those of EILV isolate (90.4 %) and Mwinilunga alphavirus (75.5 %). EILV zmq19_M44 attained a saturating titer in C6/36 cells at 6–8-days post infection but was unable to replicate in mammalian cells. Phylogenetic analysis revealed the Zambian SINV (strain zmq17_M115) belongs in Clade D of SINV Genotype 1 along with the Kenyan isolate BONI 584 from Central Africa. The growth of the SINV zmq17_M115 was comparable to that of the prototype SINV strain AR339 in mammalian cells but was statistically different in insect cells. Our findings will contribute to public health measures for the control of alphaviral diseases in Zambia.